Ottawa Paper - The Wear of Rails as Related to their Sections - P. H. Dudley (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1890)
The present paper was suggested by the paper read by Mr. R. W. Hunt at the New York Meeting, in February last, on rail-sections (Trans., xvii., p. 778)) in the discussion of which I brought forward some of the facts and observations here stated. Professional duties having prevented me from writing out my part of that discussion in time for its publication in the volume containing Mr. Hunt's paper, I take the opportunity to present it in separate form and greater fulness. The striking features of the series of rail-sections submitted by Mr. Hunt are their shallow heads and heavy bases. In these respects they are quite similar to the section of the 80-1b. rail, which I designed in 1883 to meet the requirements of the traffic of the New York Central and Hudson River Railroad. Before the adoption of the 80-1b. rail, this road had modified its 65-1b. section from a shallow head with rounding sides and quite heavy base to one having a deep head and thin base. All the leading railroads had changed from the earlier sections of steel rails to those having deep heads and thin bases, conforming to the recommendations of the Committee on Rails of the American Society of Civil Engineers. It is but proper to say that the committee's investigations upon the wear of rails were made upon the rails manufactured under a practice quite different from that which obtained after the committee's recommendations were carried into effect. The results in actual service have been contrary to what was expected. Fig. 1 shows my 80-1b. section of 1883. Before designing this rail I had taken, at different times, a series of diagrams of the condition of tracks, with my car, on the New York Central and Hudson River Railroad, all of the New England railroads, and all but one of the trunk lines. My diagrams gave me an opportunity which could not otherwise have been obtained to see the wear of great numbers of sections of rails under widely varying conditions of traffic.